Variables Associated With Administration of Nurse-initiated Analgesia in Pediatric Triage. Issue 5 (May 2020) - Shavit, Itai; Hecht-Sagie, Lior; Allon, Raviv; Leiba, Ronit; Barbi, Egidio; Poonai, Naveen; Shavit, Danielle; Feldman, Oren
Abstract : Objectives: Triage nurse-initiated analgesia (TNIA) has been shown to be associated with decreased time to the provision of analgesia and improved patient satisfaction. We examined variables that influence the provision of analgesia in a pediatric emergency department that uses TNIA. Methods: A 4-year retrospective cohort study of all children with triage pain scores ≥1 was conducted. Data on demographics and patients' and nurses' characteristics were collected. Logistic regression analyses were used to examine the effect of multiple variables on the provision of any analgesia and opioid analgesia. Results: Overall, 28, 746 children had triage pain scores ≥1; 14, 443 (50.2%) patients received analgesia of any type and 1888 (6.6%) received opioid analgesia. Mean time to any analgesia was 8.0±3.7 minutes. Of the 9415 patients with severe pain, 1857 (19.7%) received opioid analgesia. Age, sex, hourly number of patients waiting to be triaged, and nurse experience were not associated with the provision of any analgesia or opioid analgesia. Severe pain had the highest odds ratios (ORs) for the provision of any analgesia and opioid analgesia (7.7; 95% confidence interval [CI]: 7.1-8.2 and 22.8; 95% CI: 18.1-28.8, respectively). Traumatic injury and time-to-triage <8 minutes were associated with the provision of opioid analgesia (OR: 4.7; 95% CI: 4.2-5.2 and OR: 1.6; 95% CI: 1.5-1.8, respectively). Discussion: TNIA yielded a short time to analgesia, but rates of any analgesia and opioid analgesia were low. Several variables associated with the provision of any analgesia and opioid analgesia were identified. Our findings provide evidence to guide future educational programs in this area. Abstract : Supplemental Digital Content is available in the text.